2020
DOI: 10.1159/000508784
|View full text |Cite
|
Sign up to set email alerts
|

Neuroblastoma Amplified Sequence Gene Mutations Inducing Acute Kidney and Liver Injury in an Adolescent Female

Abstract: Acute liver injury (ALI) in children is a life-threatening event, and a definitive etiology can be identified in approximately 50% of cases. Neuroblastoma amplified sequence (NBAS) gene mutations have been associated with a broad phenotypic spectrum of this disease, ranging from recurrent episodes of fever-induced liver injuries to multiorgan involvement, including frequent infections as well as skeletal and immunological abnormalities. Here, we describe an adolescent female with a confirmed compound heterozyg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…Several mutations have been previously reported, such as the missense mutations in the NBAS genes, which constitute c.2674G>T, c.1018G>C, and the c.5741G>A mutations [19][20][21][22][23][24][25][26]. These mutations affect the evolutionarily conserved amino acids and can be very damaging thus resulting in liver dysfunction and Pelger-Huet anomaly [18].…”
Section: Discussionmentioning
confidence: 99%
“…Several mutations have been previously reported, such as the missense mutations in the NBAS genes, which constitute c.2674G>T, c.1018G>C, and the c.5741G>A mutations [19][20][21][22][23][24][25][26]. These mutations affect the evolutionarily conserved amino acids and can be very damaging thus resulting in liver dysfunction and Pelger-Huet anomaly [18].…”
Section: Discussionmentioning
confidence: 99%
“…The NBAS protein is broadly expressed in various organs, including the liver, heart, skeletal muscle, and leukocytes. Many studies reported that NBAS gene mutations were associated with infantile failure syndrome 2 (ILFS2), a fever-induced multi-systemic syndrome known as short stature with optic atrophy and Pelger-Huët anomaly (SOPH) syndrome, and immunode ciency [4,5]. Here, we report the possible rst case of RALF caused by a novel compound heterozygous mutation in the NBAS gene that underwent living donor liver transplantation (LDLT) in China.…”
Section: Introductionmentioning
confidence: 99%